Ligation, Transformation and Characterization of Rv 1926c Mycobacterium tuberculosis to Escherichia coli JM 109 For Latent Tuberculosis Immunodiagnostic - Rosana Agus (International Journal of Applied Biology, 2018)
Tuberculosis caused by Mycobacterium tuberculosis is the biggest infectious disease causing human death in the world. The main challenge in controlling tuberculosis is to quickly and accurately diagnose tuberculosis infection. Several kits have been produced to diagnose tuberculosis, but have different sensitivity and specificity. This shows that the kit is not yet ideal for diagnosing tuberculosis, so the search for candidates for specific antigens still needs to be done. One potential antigen is the Rv 1926c encoding MPT 63 protein. This protein is known to induce Th1 cells and produce IFN λ from PBMC cells of patients infected with tuberculosis. The purpose of this study was to clone the Rv 1926c from Mycobacterium tuberculosis as a tuberculosis immunodiagnostic kit. The method used is isolating Rv 1926c with PCR, ligation to pGEM-T vector and transformation to E.coli host cell JM 109. Clone characterization was carried out by PCR and migration analysis. The results obtained are the recombinant clones obtained have successfully inserted with the Rv 1926 c